Influence of Parkinson’s Disease on Judging Stair Step Height: Exploratory Study - da Conceição, Núbia R. [UNESP]; Teixeira-Arroyo, Claudia [UNESP]; Vitório, Rodrigo [UNESP]; Orcioli-Silva, Diego [UNESP]; Beretta, Victor S. [UNESP]; de Sousa, Priscila N. [UNESP]; Gobbi, Lilian T. B. [UNESP] (SAGE Publications, 2019)
This study investigated the effects of Parkinson’s Disease (PD) on the perceptive judgment of stair step height using both exteroceptive visual and exproprioceptive judgments. We invited 14 individuals with PD and 14 neurologically healthy older adults (OA) to perform perceptual judgment tasks for first step stairway heights of 11 and 20 cm. Initially, participants performed first the exteroceptive visual judgment and then the exproprioceptive judgment in five randomized trials for each stair height. An analysis of variance for the exteroceptive visual judgment revealed no main effects or interaction between PD versus OA groups and height. However, the analysis of variance for exproprioceptive judgment revealed a significant interaction between group and height (F 1,26 = 9.519; p =.005; Pη 2 =.268) such that both groups made more errors in exproprioceptive judgment at a height of 11 cm. The OA group made more errors in exproprioceptive judgment for the 20-cm step when compared with the PD group (p =.016) but the PD group underestimated the step height. We conclude that PD influences exproprioceptive perception of step height and that steps with smaller (vs. larger) heights induce greater exproprioceptive error.
Keywords: exproprioceptive judgment; exteroceptive judgment; gait; movement disorders; neurodegenerative disorders